2004
DOI: 10.1038/sj.onc.1207794
|View full text |Cite
|
Sign up to set email alerts
|

Serine 518 phosphorylation modulates merlin intramolecular association and binding to critical effectors important for NF2 growth suppression

Abstract: The neurofibromatosis 2 (NF2) tumor suppressor protein, merlin, functions as a negative growth regulator; however, the molecular mechanisms that underlie merlin regulation remain elusive. Recent studies have implicated merlin phosphorylation in regulating merlin subcellular localization and growth suppression. P21-activated kinase (PAK), a downstream target of Rac1/Cdc42, directly phosphorylates merlin at Serine 518. In this report, we show that PAK2 directly phosphorylates wild-type merlin, whereas merlin tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 38 publications
4
109
1
Order By: Relevance
“…Nevertheless, the closed form of Merlin has recently been shown to suppress tumorigenesis by translocating to the nucleus, where it inhibits the E3 ubiquitin ligase CRL4 DCAF1 [35]. These findings are fully consistent with the widely held view that only the closed form of Merlin is able to suppress tumorigenesis [43,50,52] and with reports suggesting that Merlin shuttles in and out of the nucleus [68,69]. However, most previous studies had failed to detect Merlin in the nucleus, possibly because the antibodies used are directed against an epitope of nuclear Merlin that is masked under standard fixation and permeabilization conditions.…”
Section: Merlin Localizationsupporting
confidence: 85%
“…Nevertheless, the closed form of Merlin has recently been shown to suppress tumorigenesis by translocating to the nucleus, where it inhibits the E3 ubiquitin ligase CRL4 DCAF1 [35]. These findings are fully consistent with the widely held view that only the closed form of Merlin is able to suppress tumorigenesis [43,50,52] and with reports suggesting that Merlin shuttles in and out of the nucleus [68,69]. However, most previous studies had failed to detect Merlin in the nucleus, possibly because the antibodies used are directed against an epitope of nuclear Merlin that is masked under standard fixation and permeabilization conditions.…”
Section: Merlin Localizationsupporting
confidence: 85%
“…As MMs are highly aggressive and invasive tumors, we investigated the effects of re-expressing merlin in two MM cell lines (Meso17, Meso25) that lack expression of endogenous NF2. We and others have previously shown that phosphorylation of merlin on Serine 518 leads to relocalization and inactivation of the protein, whereas an unphosphorylatable mutant (NF2-518A) functions as a constitutively active protein (Rong et al, 2004;Surace et al, 2004;Xiao et al, 2005). In cells, the availability of active, hypophosphorylated merlin is limited and tightly controlled (Lallemand et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the head-to-tail-bound/ closed form of merlin is required for its tumorsuppressing activity (Sherman et al, 1997;Gutmann et al, 1999a;Rong et al, 2004). The first 50 amino acids of merlin, which are required for the inhibition of the CD44-HA interaction and of the s.c. growth of Tr6BC1 cells, are located at the NH 2 -terminal extremity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the interaction between the NH 2 -and COOH-terminal halves of merlin maintains merlin in the closed configuration that is required for its tumor-suppressor activity, and that phosphorylation of S518 interferes with the interaction between the NH 2 -and COOH-terminal halves of merlin and inactivates its tumor-suppressor activity (Sherman et al, 1997;Rong et al, 2004;McClatchey and Giovannini, 2005). To assess how the NH 2 -terminal merlin mutations (Del-1-Del-5) interact with the COOH-terminal half of the molecule, we established a fusion construct between GST (pGEX4T1 vector, Amersham) and the COOHterminal half of merlin (merlin ).…”
Section: Increased Expression Of Merlin Inhibits the Binding Of Fluormentioning
confidence: 99%